Effectiveness of Zhong‐Yong thinking based dialectical behavior therapy group skills training versus supportive group therapy for lowering suicidal risks in Chinese young adults: A randomized controlled trial with a 6‐month follow‐up. Issue 6 (18th April 2020) - Yang, Xueling; Liu, Ding; Wang, You; Chen, Yu; Chen, Weichen; Yang, Caiyan; Zhang, Peining; Ding, Siyuan; Zhang, Xiaoyuan
Abstract: Background: Dialectical behavior therapy (DBT) is a first‐line treatment for the prevention of suicide. Zhong‐Yong thinking could be viewed as a Chinese way of dialectical thinking, has long been a culturally dictating thinking style in China. To enhance cultural adaptability, we integrated Zhong‐Yong thinking into DBT group skills training and examined its efficacy in suicidal prevention compared with a supportive group therapy and a wait‐list group in high‐risk suicidal Chinese college students. Methods: A total of 97 suicidal participants were randomized to either Zhong‐Yong thinking based DBT group skills training (DBTZYT, n  = 33), or supportive group therapy (SGT; n  = 32), or wait‐list group (WL; n  = 32). DBTZYT was a 12‐week program based on Zhong‐Yong thinking instead of dialectical thinking, coaching participants mindfulness, emotion regulation, distress tolerance, and interpersonal effectiveness. Supportive group therapy was a 12‐week program aiming at improving interpersonal effectiveness and emotion regulation skills. Outcome measures were assessed at pre‐ and post‐treatment and 6‐month follow‐up. Results: At post‐treatment measures, the levels of suicidal ideation, hopelessness, psychache symptoms, and general psychopathology had significantly decreased in both intervention groups; at the 6‐month follow‐up measures, the intervention effects were better maintained in the DBTZYT group rather than in the SGT group. Specifically, DBTZYT was more effective in relieving participants' long‐term obsessive‐compulsive, anxiety, hostility, phobic, psychotic, and additional symptoms. Conclusions: Zhong‐Yong thinking not only could integrate with DBT skills training in Chinese young adult population, but also has special strength in enhancing DBT's efficacy. Abstract : Zhong‐Yong thinking is a Chinese way of dialectical thinking Zhong‐Yong thinking based dialectical behavior therapy (DBT) lowered suicidal risks Zhong‐Yong thinking has special strength in enhancing DBT's efficacy.